The STUNTING PREVENTION THROUGH INCREASING KNOWLEDGE OF PREGNANT WOMEN AND KADER - Yulianie, Rany (Universitas Gajah Putih, Indonesia, 2023)
Stunting is a health problem caused by a lack of nutritional intake. Stunting is characterized by height that does not match their age. Stunting can even occur in babies/fetuses who are malnourished while in the womb, therefore stunting can be prevented indirectly during pregnancy. Prevention of stunting can be done one way or another through increasing knowledge of pregnant women as the main object and cadres as a driving factor in a change in health behavior. The purpose of this health service is to provide education on stunting and prevention of stunting in pregnant women. The result of this dedication was an increase in knowledge from partners after being given counseling about stunting and its prevention in pregnant women with an average pre-test score of 83.3 and a post-test score of 92.5, which means that it has an increase in average score of 9.2. As well as the Wilcoxon test with a sig value of 0.000 < α 0.05, the counseling activities carried out are effective and influential in increasing partners' knowledge. It is hoped that partners can always increase their knowledge, especially regarding stunting and its prevention during pregnancy, so that a stunting-free generation is born.